Obstacles to ethical decision-making : mental models, Milgram and the problem of obedience - Werhane, Patricia Hogue (Cambridge : New York ; Cambridge University Press, 2013)
"In commerce, many moral failures are due to narrow mindsets that preclude taking into account the moral dimensions of a decision or action. In turn, sometimes these mindsets are caused by failing to question managerial decisions from a moral point of view, because of a perceived authority of management. In the 1960s, Stanley Milgram conducted controversial experiments to investigate just how far obedience to an authority figure could subvert his subjects' moral beliefs. In this thought-provoking work, the authors examine the prevalence of narrow mental models and the phenomenon of obedience to an authority to analyse and understand the challenges which business professionals encounter in making ethical decisions. Obstacles to Ethical Decision-Making proposes processes - including collaborative input and critique - by which individuals may reduce or overcome these challenges. It provides decision-makers at all levels in an organisation with the means to place ethical considerations at the heart of managerial decision-making"--
"Patricia H. Werhane is the Callista Wicklander Chair of Business Ethics and Director, Institute for Business and Professional Ethics at DePaul University. She was formerly the Peter and Adeline Ruffin Chair of Business Ethics and Senior Fellow at the Olsson Center for Applied Ethics in the Darden Graduate School of Business Administration at the University of Virginia, where she is now Professor Emeritus. Until 1993, she was the Henry J. Wirtenberger Professor of Business Ethics at Loyola University of Chicago. She received her B.A. from Wellesley College, and M.A. and Ph.D. from Northwestern University"--
Machine generated contents note: 1. Introduction; 2. The role of mental models in social construction; 3. The Milgram studies: obedience, disobedience, and ethical context; 4. Obstacles to ethical decision-making in the perception of ethical context; 5. Obstacles to ethical decision-making in impact analysis and action; 6. Managing ethical obstacles; 7. Problematic mental models: some applications; 8. Conclusion.
Includes bibliographical references (pages 213-234) and indexes.
Keywords: Business ethics; Decision making -- Moral and ethical aspects; BUSINESS & ECONOMICS / Business Ethics